The Effect of Foreign Investment Mediation on Economic Growth in Indonesia - Larasati Shabna Azis; Abd Hamid Paddu; Indraswati Tri Abdi Reviane (Lafadz Jaya Publisher, 2023)
This research aims to test and analyze the influence of foreign investment mediation towards economic growth in Indonesia. This research uses a quantitative approach. The data used is secondary data. Data collection in this study is through quarterly annual report from Badan Pusat Statistik, Bank Indonesia, dan Badan Koordinasi Penanaman Modal. The analysis method used is path analysis using the SPSS program version 25.0. The result of this study showed that, 1) inflation has no effect directly on economic growth, or indirectly through foreign investment mediation, 2) interest rate has negative and significant effect directly on economic growth, however interest rate has positive and significant effect indirectly on economic growth through foreign investment mediation, 3) exchange rate has no effect directly on economic growth, however exchange rate has negative and significant effect indirectly on economic growth through foreign investment mediation.